VARIABEL – VARIABEL YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMBELI PRODUK FINGER PRINT DIZ TECH INDONESIA - Fajar, Erry Nur; dwi, jojok (Jurnal Bisnis Indonesia, 2017)
Analysis method used in this study quantitative descriptive method, simultaneous This study aimed to analyze the effect of the decision variables posed by consumers of the product variable, the variable price, location variables and variable promotion of consumer decision in buying finger print products at Z Tech Indonesia This study using purposive sampling technique then selected sample of 100 people and the object of this study is that mebeli consumer finger print products at Z Tech Indonesia. The analysis and partial (multiple linear regression analysis using SPSS). Based on the results of the analysis of multiple linier regression then it can be determined that free variables are simultaneously examined have a significant influence on the buying decision variables, while partially indicate that the variable products, variable pricing, and location variable has a significantly to the purchase decision variables, only the variable promotional that has no effect significant influence on the purchase decision variables. Variable products have the most significant influence on purchasing decisions. While most small pricing variables significantly influence the purchase decision. Not all independent variables or independent variables influence, so it can be concluded that the only variable that affects the location of simultaneously against the decision to buy the product at Z Tech Indonesia.   Keywords: Purchasing Decision, Product Variables, Variable Rates, Variable Area, Variable Promotion